Experimental Investigation of FGM Dental Implant Properties Made from Ti/HA Composite - Mohammad Sedighi; Narges Omidi; Amirhossein Jabbari (Mechanics of Advanced Composite Structures)
Although titanium/hydroxyapatite composite is an attractive material for dental implants, it would be more useful if it could be produced as a functionally graded material (FGM). In this paper, microstructure and microhardness of a five-layer titanium/hydroxyapatite functionally graded material has been investigated. First, titanium and hydroxyapatite (HA) powders were mixed with the Ti to HA volume ratios of 100:0, 90:10, 80:20, 70:30 and 60:40. Next, the obtained powders were poured into a graphite mold functionally and then sintered using spark plasma sintering (SPS) method. Microhardness and microstructure of the samples was examined using Vickers microhardness test and optical microscopy. The results show that HA particles have an acceptable distribution in the matrix. Also, average matrix grain size increased in Ti/HA composites compared to the pure Ti layer. Moreover, the layers with 30 and 40 vol% HA have the highest and the lowest microhardness, respectively.